Asal Usul dan Implementasi Ahli Waris Pengganti Perspektif Hukum Islam - M., Hajar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
The existence of substitute heir still causes polemics either in the side of its derivation or in its validity.The substitute heir in KHI is formulated through yurisprudence which is taken from customary law. The substitute heir in customary law is an adoption of civil law (BW) of Dutch derived from Code Civil Napoleon in French. French’s civil law was born of romen’s law.The substitute heir develops toovercome the matters partaining to inheritance either in the level ofheir, traditional deliberation,  or  judicature  institution.  The substitute  heir  is  a  culture which is not based on faith, contrary to judicature principle, ijbari basic, not accordance with the elements pertaining inheritance  and it is also contrary  to  superiority  and  hijab  principle.  Therefore,  it  needs  to review.